The History of Money in Montenegro - Nikola Fabris (Journal of Central Banking Theory and Practice, 2015)
The paper depicts the history of using money in Montenegro covering the period before the Christ until nowadays. Montenegro mostly used foreign currencies throughout its long history, these being Roman, Austro-Hungarian, Turkish, Venetian, and even the Napoleon (French gold coin) money. The first ideas for Montenegro's own money came from the Bishop Petar Petrovic Njegoš in the 19th century. The first Montenegrin money, the Perper, was minted in 1906. The King Nikola's Decree as of 11 April 1906 authorized the Ministry of Finance to mint the nickel and bronze coins. Silver and gold coins were minted later. The Perper disappeared from the scene with Montenegro's joining the Kingdom of Serbs, Croats and Slovenes, putting into circulation the Dinar, a currency of the newly established state. Montenegro, being a part of the Socialist Federal Republic of Yugoslavia, used the Dinar as its currency after World War II until 1999. Dual currency system consisting of the German Mark and the Dinar was introduced in late 1999, whereby the German Mark became the only legal tender in 2001. With the introduction of the Euro the German Mark was replaced and the Euro became the official means of payment.
Keywords: E51; E40; 330; Montenegro; Money; Perper; Euro; History